Multicomponent multiproduct closed-loop supply chain design with transshipment and economies of scale considerations. (March 2021) - Samuel, Christian N.; Diallo, Claver; Venkatadri, Uday; Ghayebloo, Sima
Highlights: A closed-loop supply chain design model with transshipment and economies of scale is developed. Multiple multicomponent products with different parts reliability flow across the network. Multiple suppliers, customer zones, reprocessing plants and a recycling center are included. Component reliability, economies of scale and transshipment affect the network design and profits. Interactions between disassembly capacity, parts reliability and demand for refurbished are shown. Abstract: With the growing awareness for sustainability, organizations have engaged in multiple initiatives to recover, remanufacture and extend the lifecycle of their products. The resulting closed-loop supply chains (CLSC) have been considerably studied under various conditions. This paper proposes an integrated model for the design of a multi-component multi-product CLSC with economies of scale for the location of processing centers, transshipment of inspected products between centers, and reliability of returned products. Multiple numerical experiments are run to show the impact of part reliability, economies of scale and transshipment on the network design decisions. When returned products or parts are highly reliable, it is found that Inspection, Refurbishment and Disassembly centre (IRDC) capacity is lower because more products are available for refurbishing or for the recovery of parts through disassembly. However, when reliability is low, greater IRDC capacity is required. This can be achieved by either increasing their number or size. In the case of the latter, it is noted that Economies of Scale (EOS) come into play. Since IRDCs are geographically dispersed in the supply chain, any network configuration model should allow for transshipment because when larger IRDCs are chosen as a result of EOS incentives, fewer of them are needed, which in turn implies transshipment between IRDCs.